Vulnerability modelling with functional programming and dependent types. (15th December 2014) - IONESCU, CEZAR
Abstract : We present an interdisciplinary effort in the field of global environmental change, related to the understanding of the concept of 'vulnerability'. We have used functional programming to capture the generic aspects of the myriad of definitions of vulnerability, and have used the resulting formalization to learn something new about vulnerability and to write some better software for vulnerability assessment. In the process, we have also found out something about formalization in general, about the advantages and disadvantages of dependent types, and about the role of computing science in the larger intellectual landscape.